PJMHS 2022
DOI: 10.53350/pjmhs22168853
|View full text |Cite
|
Sign up to set email alerts
|

Functional Outcome of Closed Static Intramedullary Nailing with Distal two Plane Locking Versus Percutaneous Mippo Distal Tibial Locking Plate in Distal 3rd Tibia Metaphyseal Fractures

Abstract: Objective: Aim of current study was to determine the functional outcomes of closed static intramedullary nailing with distal two plane locking versus percutaneous MIPPO distal tibial locking plate in distal 3rd tibia metaphyseal fractures. Study Design: Randomized clinical trial Place and Duration: Nishtar Hospital Multan/Qaisrani Medical Center Multan. Jan 2021-March 2022 Methods: There were 76 patients of both genders with age 15-60 years presented. All the patients had 3rd tibia metaphyseal fracture were ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…[15,16] This observation aligns with existing research emphasizing the importance of minimizing radiation exposure during surgical procedures to protect healthcare professionals. [17,18] Additionally, our study revealed a reduction in surgical duration. [19] Previous studies align with this finding, indicating that decreased surgical time can reduce patient trauma and lower healthcare costs.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…[15,16] This observation aligns with existing research emphasizing the importance of minimizing radiation exposure during surgical procedures to protect healthcare professionals. [17,18] Additionally, our study revealed a reduction in surgical duration. [19] Previous studies align with this finding, indicating that decreased surgical time can reduce patient trauma and lower healthcare costs.…”
Section: Discussionsupporting
confidence: 56%
“…[ 15 , 16 ] This observation aligns with existing research emphasizing the importance of minimizing radiation exposure during surgical procedures to protect healthcare professionals. [ 17 , 18 ]…”
Section: Discussionmentioning
confidence: 99%